Application of Resource Migration on Housing Fund Archives System - Changxing Qi (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper analyzes the feature and necessity of resource migration, and summarizes the commonly methods among different systems. According to the requirements of the systems in the housing fund center,an architecture model based on resource migration is designed. The process of migration, the format and specification of the data packet are described according to the architecture levels and the process.After the migration application is developed,the operation data of the system are analyzed and further suggestions are given. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5392